Lista recenzentów rocznika 2014: - SP, Redakcja (Studia Psychologica: Theoria et praxis, 2014)
Agata Błachnio Piotr Francuz Tomasz Kopczyński Dariusz Krok Wiesława Limont Anna Matczak Krzysztof Mudyń Marek Nieznański Andrzej Pankalla Zofia Rosińska Paweł Maria Socha Krzysztof Stachewicz Andrzej Strzałecki Dorota Szczygieł Magdalena Śmieja-Nęcka Zenon Uchnast Krystyna Węgłowska - Rzepa Beata Zarzycka